2016
DOI: 10.1097/j.pain.0000000000000731
|View full text |Cite|
|
Sign up to set email alerts
|

Racial and ethnic differences in experimental pain sensitivity: systematic review and meta-analysis

Abstract: Our objective was to describe the racial and ethnic differences in experimental pain sensitivity. Four databases (PubMed, EMBASE, the Cochrane Central Register of Controlled Trials, and PsycINFO) were searched for studies examining racial/ethnic differences in experimental pain sensitivity. Thermal-heat, cold-pressor, pressure, ischemic, mechanical cutaneous, electrical, and chemical experimental pain modalities were assessed. Risk of bias was assessed using the Agency for Healthcare Research and Quality guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
120
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(146 citation statements)
references
References 62 publications
13
120
5
1
Order By: Relevance
“…Differences in demographic characteristics-such as age, gender, BMI, and race-have been shown to lead to variability of pain sensibility. [35][36][37][38] In our present work, we also demonstrated that demographic characteristics were indispensable predictors of pain thresholds. EPT and PPT are often used in quantitative assessment of pain sensitivity in clinical studies.…”
Section: Discussionsupporting
confidence: 76%
“…Differences in demographic characteristics-such as age, gender, BMI, and race-have been shown to lead to variability of pain sensibility. [35][36][37][38] In our present work, we also demonstrated that demographic characteristics were indispensable predictors of pain thresholds. EPT and PPT are often used in quantitative assessment of pain sensitivity in clinical studies.…”
Section: Discussionsupporting
confidence: 76%
“…Race/ethnic differences in clinical and experimental pain have been widely documented , and a growing literature has recognized resilience as an important resource for individuals with chronic pain . Expanding on prior research, our study provides evidence regarding the influence of psychosocial resilience on pain and functioning among adults with knee OA and is the first to examine whether these relationships are differentially expressed across race/ethnicity.…”
Section: Discussionmentioning
confidence: 80%
“…Racial/ethnic disparities in pain and disability are widely reported as non‐Hispanic blacks (NHBs) experience more frequent, severe, and disabling pain relative to non‐Hispanic whites (NHWs) . Moreover, several studies have found that NHBs report greater experimental pain sensitivity to a number of quantitative sensory testing methods when compared with NHWs . These effects also extend to OA, as NHBs experience higher rates of symptomatic and radiographic OA , report greater average pain severity, and have higher levels of disability than NHWs .…”
Section: Introductionmentioning
confidence: 99%
“…A relation between perception of pain and ethnicity has been proposed (Kim et al 2017). Of the people living in € Orebro County in 2015, 248 474 (85.4%) were born in Sweden and 42 538 (14.6%) were born abroad (www.SCB.se).…”
Section: Characteristics and Impact Of Painmentioning
confidence: 99%